The Spanish gut microbiome reveals links between microorganisms and Mediterranean diet - Adriel Latorre-Pérez (Nature Portfolio, 2021)
Abstract Despite the increasing evidence of links between human gut and health, the number of gut microbiomes that have been studied to date at a country level are surprisingly low. Mediterranean countries, including some of the most long-lived and healthy countries in the world, have not been considered so far in those studies at a large scale. The main objective of this work is to characterize the gut microbiome of a healthy adult population of a Mediterranean, paradigmatically healthy country: Spain. Stool samples from 530 healthy volunteers were collected, total metagenomic DNA extracted, and the microbial profiles determined through 16S rRNA metataxonomic sequencing. Our results confirm the associations between several microbial markers and different variables, including sex, age, BMI and diet choices, and bring new insights into the relationship between microbiome and diet in the Spanish population. Remarkably, some of the associations found, such as the decrease of Faecalibacterium with age or the link of Flavonifractor with less healthy dietary habits, have been barely noticed in other large-scale cohorts. On the other hand, a range of links between microorganisms, diet, and lifestyle coincide with those reported in other populations, thus increasing the robustness of such associations and confirming the importance of these microbial markers across different countries. Overall, this study describes the Spanish “normal” microbiome, providing a solid baseline for future studies investigating the effects of gut microbiome composition and deviations in the adherence to the Mediterranean diet.